Wordplay as a means of attraction in commercial names (based on company names of the Ternopil region of Ukraine) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article is a study of the role of wordplay as a means of attraction of clients in the structure of commercial names, of the structural and semantic-associative features of wordplay in ergonymy. It distinguishes and analyzes models of company names of the Ternopil region of Ukraine, which are formed by means of different types of wordplay.
Keywords: ergonym; company name; wordplay; pun; attraction; advertising function